Effect of DHA supplementation on oxylipin levels in plasma and immune cell stimulated blood. (June 2017) - Schuchardt, Jan Philipp; Ostermann, Annika I.; Stork, Lisa; Fritzsch, Sabrina; Kohrs, Heike; Greupner, Theresa; Hahn, Andreas; Schebb, Nils Helge
Abstract: Introduction: EPA and DHA cause different physiological effects, which are in many cases mediated via their oxidative metabolites (oxylipins). However, metabolism studies investigating the effect of either EPA or DHA on comprehensive oxylipin patterns are lacking. Material and methods: The short and long term (1, 3, 6, and 12 week) effect of 1076 mg/d DHA (free of EPA) on free (unesterified) oxylipin concentrations in plasma and lipopolysacharid (LPS) stimulated blood of 12 healthy men (mean age 25.1 ± 1.5 years) was investigated. Results: After DHA supplementation, plasma levels of all DHA-oxylipins (HDHAs, EpDPEs, DiHDPEs) significantly increased (up to 600%) in a time-dependent fashion. Oxylipins of EPA and arachidonic acid (AA) were also affected. Whereas a slight increase in several EPA-derived hydroxy-FAs (including the RvE1 precursor 18-HEPE) and dihydroxy-FAs was observed after DHA supplementation, a trend to a slight decline in AA-derived oxylipin levels was found. In LPS stimulated blood, it is shown that DHA supplementation significantly reduces the ability of immune cells to form AA-derived COX (TXB2 and PGB2) and 12-LOX (12-HETE) eicosanoids. While no increase in EPA COX metabolites was found, n-3 PUFA 12-LOX metabolites of EPA (12-HEPE) and DHA (14-HDHA) were highly induced. Conclusion: We demonstrated that DHA supplementation causes a time-dependent shift in the entire oxylipin profile suggesting a cross-linked metabolism of PUFAs and subsequent formation of oxygenated lipid mediators. Highlights: Examination of acute and long-term effect of DHA on free oxylipin levels in plasma. Up to 600% increase of DHA-oxylipins (HDHAs, EpDPEs, DiHDPEs). Changes in the entire oxylipin profile suggest a cross-linked PUFA metabolism. Slight increase in several EPA-derived hydroxy-FAs and dihydroxy-FAs. Trend to a slight decline in arachidonic acid-derived oxylipin levels.